Increased risk of postpartum depression in women with lactational mastitis: a cross-sectional study - Shen, Fuyi; Zhou, Xianjin; Guo, Fei; Fan, Kechen; Zhou, Yilu; Xia, Jianhua; Xu, Zhendong; Liu, Zhiqiang (Frontiers in Psychiatry, 2023)
Background A high incidence of lactational mastitis mainly occurs during the first month of breastfeeding. It may cause severe pain, frustration, fatigue, stress, and breastfeeding concerns. However, few studies investigated the effects of lactational mastitis on postpartum depression. This study investigated the potential association between lactational mastitis and postpartum depression. Methods We examined the associations of lactational mastitis with postpartum depression in 1,551 Chinese women. Lactational mastitis was diagnosed by breast specialists. The presence of depression symptoms was evaluated by the Edinburgh Postnatal Depression Scale (EPDS) and Patient Health Questionnaire 9 (PHQ9) at 6 weeks after delivery. Multiple linear regression analysis and multivariable log-binomial regression analysis were performed to estimate the association between lactational mastitis and postpartum depression. Results Among the 1,551 mothers, 147 (9.5%) experienced lactational mastitis diagnosed by breast specialists during the postpartum period. Compared with women without lactational mastitis, the proportion of women with depression symptoms was significantly higher (38.1% vs. 27.4%, p = 0.008), and the risk of postpartum depression increased by 68% (RR = 1.68, 95% CI, 1.18, 2.40) in women who had experienced lactational mastitis. In addition, the risk of self-harm or suicidal ideation increased by 89% (RR = 1.89, 95% CI, 1.08, 3.29) in women who experienced lactational mastitis. In stratified analysis, the associations of lactational mastitis with postpartum depression appeared stronger among women aged ≥35 years, with maternal comorbidities, and who delivered a female neonate. Conclusion The study results suggest that lactational mastitis is a risk factor for depression during the postpartum period. The impact of lactational mastitis on maternal mental health requires further attention. Clinical trial registration chictr.org.cn, ChiCTR2000041519.